AFSOS-SFRO-SFH-SFNEP-SFCE-GFRP guidelines on radio-induced nausea and vomiting. (December 2022) - Faivre, JC.; Tomaszewski, F.; Demoor-Goldschmitt, C.; Beddok, A.; Malgras, A.; Schmitt, A.; Fabre, J.; Perrot, A.; Jovenin, N.; Salleron, J.; Clavère, P.; Pointreau, Y.; et al.
Abstract: Introduction: The prevalence of radiation-induced nausea and vomiting varies between 40% and 80%. They have many consequences on treatment and comorbidities. This work thus aimed to define clinical practice guidelines for the management of radiation-induced nausea and vomiting. Methods: XXXXX, XXXX, XXX, XXXXX, XXXX and XXXX compiled a working group who draft these recommendations. Results: The assessment of the emetogenic risk found two main predictive factors: 1) the irradiated anatomical location, 2) an associated concomitant chemotherapy. In the case of exclusive radiotherapy, primary antiemetic prophylaxis depends on the emetogenic risk (the irradiated anatomical location). In the case of concomitant chemotherapy, the emetogenic risk is generally higher and the primary antiemetic prophylaxis corresponds to that of chemotherapy-induced nausea and vomiting. In cases where symptoms persist, remedial treatments are poorly codified. Conclusion: Radiation-induced nausea and vomiting remains underdiagnosed and undertreated, its rapid detection and treatment are essential to reinstate good clinical practice. Graphical Abstract: ga1 Highlights: The incidence of radiation-induced nausea and vomiting varies between 40% and 80% and depends on the irradiated anatomical location and on the presence or not of concomitant chemotherapy. In the case of exclusive radiotherapy, primary antiemetic prophylaxis depends on the emetogenic risk represented by the anatomical location of irradiation. In the case of concomitant radiochemotherapy, the emetogenic risk from the chemotherapy is generally higher and thus primary antiemetic prophylaxis focuses on the chemotherapy-induced nausea and vomiting. If primary prophylaxis fails, the differential diagnoses should be ruled out. Breakthrough treatments are poorly codified. Radiation-induced nausea and vomiting among the paediatric population is poorly studied: compared to adults, children tend to tolerate abdominal irradiation better but encephalic and cranio-spinal irradiations less well.